Genetic Association Between RFC1 Gene Polymorphism (rs1051266) and Non-Syndromic Cleft Lip and Palate in the South Indian Population: A Case Control Study - Felicita, A. Sumathi (2025)
To identify whether an association exists between RFC1 gene polymorphism (rs1051266) and the development of non-syndromic cleft lip and palate. Twenty-five patients with non-syndromic cleft lip and palate (NSCL/P) with ages ranging from 1 year to 17 years belonging to both genders (Group 1) and twenty-five patients without cleft lip and palate malformations as controls (Group 2) were included in the study. Genomic DNA was obtained from whole blood drawn from the patients. The region around the RFC1 gene polymorphism was amplified with sequence-specific primers using polymerase chain reaction (PCR). RFLP technique was used to identify the genotype of the patients. The genotype and allele frequency distributions in both groups were determined. Statistical analysis was done with the Chi-square test. In both groups, the frequency of the GA genotype was greater compared to the GG genotype and AA genotype. There was no statistically significant deviation from Hardy Weinberg Equilibrium with a P value of <0.247 and <0.815 in the case and control groups, respectively. The frequency distribution of the dominant genotype GG had an odd ratio of 0.3506 (0.0791-1.5544) and a P value of 0.1678 and the recessive genotype AA had an odd ratio of1.5556 (0.4187-5.7795) and a P value of 0.5094. The distribution of G allele and A allele between the two group had an odd ratio of 0.6169 (0.2798-1.3597)and a P value of 0.2309. Classification of the genotypes based on genetic models such as dominant, recessive, or additive did not present any significant association between the polymorphism marker and NSCL/P. There was no significant association between RFC1 gene polymorphism (rs1051266) and NSCL/P in the South Indian population.